Adoção de pronunciamentos internacionais na formação de contadores em universidades peruanas - Diaz-Becerra, Oscar Alfredo (2024)
Objective: To analyze the extent to which the International Training Pronouncements have been incorporated into the profile of the graduate and the study plans of the Accounting program in Peruvian universities. Methods: The research was conducted using a descriptive and non-experimental design, applying content analysis techniques to the profile of the graduate and the study plans of a population and sample of 62 Peruvian universities offering degrees in Accounting, without excluding any units. Data analysis involved classifying into three categories, processed using Excel. Results: It is evident that there is a lack of timely updates in the majority of graduate profiles and study plans analyzed, as well as limited incorporation of technical competencies and professional skills required by the International Training Pronouncements. Conclusion: The absence of timely updates to graduate profiles and study plans in the Accounting program negatively impacts the provision of quality education, aligned with employer demands, as well as the insufficient incorporation of technical competencies and professional skills required by international standards.